The cloud revolution : how the convergence of new technologies will unleash the next economic boom and a roaring 2020s - Mills, Mark P. (New York : Encounter Books, 2021)
"When it comes to predicting how technology changes our near future, there are two camps. One says we live at a time of a "new normal" where we've netted all the low-hanging fruit and ordering a ride or food on a smartphone is as good as it's going to get. The other camp sees lots of changes but mainly in destroying jobs and traditional businesses. They're both wrong, predicts Mark P. Mills, whose earlier book "The Bottomless Well" debunked the bleak consensus view that the world had reached "peak oil" production in the early 2000s. History will record the 2020s as one of the episodic pivots in human progress where technology-driven prosperity goes into high gear. And it doesn't come from any single 'big' invention, but from the convergence of radical advances in technologies in three domains: the "Cloud," history's biggest and newest infrastructure, built from next-generation microprocessors and democratizing artificial intelligence; new kinds of machines used for making and moving everything; and the emergence of unprecedented and novel materials from which everything is built. We've seen this pattern before. The structure of the technological revolution that drove the last long-run expansion can be traced to the 1920s. It too came from the same kind of convergence: a new information infrastructure (telephony), new machines (cars and power plants), and new materials (plastics and pharmaceuticals). It's true that we've wrung all the magic out of the last boom. But the next one starts now. The U.S. is again at the epicenter of these innovations, one that promise to upend the status quo in manufacturing, transportation, healthcare, education, energy and entertainment"--
Pt. I. Technology forecasting. Technology matters ; The structure of technological revolutions -- pt. II. Biggest infrastructure ever built. Silicon engines: the end of 'computers' ; Information as infrastructure -- pt. III. Revolutions in technology's three spheres: information, machines, materials. The information: the knowledge boom ; The information: digitalizing commerce ; The information: digitalizing science ; The materials: from dematerializing to rematerializing ; The materials: from harvesting to synthesizing ; The materials: the energy nexus ; The machines: human amplifiers ; The machines: the magic in movements ; The machines: means of production ; The machines: energizing everything ; The machines: automation to automatrons -- pt. IV. The roaring 2020s. Work: the 'end of work' myth ; Work: the servicification of manufacturing ; Work: robotification of services ; Work: freight drones, silicon cars & Uber air ; Health: the cure in the code ; Health: the future won't be like Star Trek, it will be better ; Health: the robotification of (health) services ; Education and entertainment: down the (same) rabbit hole? ; Education: the telecommuting tutor ; Education: virtualizing 'soft' skills for 'dirty jobs' ; Entertainment: from Euripides to E-sports ; Entertainment: the 'means' of amusements ; Science: the pursuit of miracles ; Science: the 'neurotechnic' era -- What could possibly go wrong?: climate, China & tech barons -- Appendix: the business of futurism.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 15, 2023).
eBooks on EBSCOhost
Keywords: Industry 4.0.; Technological forecasting; Cloud computing -- Economic aspects; Automation; Automation; Industrie 4.0.; Prévision technologique; Infonuagique -- Aspect économique.; Automatisation; automation; Automation; Industry 4.0; Technological forecasting